Empirical studies of collaborative information seeking: a review of methodological issues. Issue 1 (14th January 2019) - Hertzum, Morten; Hansen, Preben
Abstract : Purpose: Information seeking is often performed in collaborative contexts. The research into such collaborative information seeking (CIS) has been proceeding since the 1990s but lacks methodological discussions. The purpose of this paper is to analyze and discuss methodological issues in existing CIS studies. Design/methodology/approach: The authors systematically review 69 empirical CIS studies. Findings: The review shows that the most common methods of data collection are lab experiments (43 percent), observation (19 percent) and surveys (16 percent), that the most common methods of data analysis are description (33 percent), statistical testing (29 percent) and content analysis (19 percent) and that CIS studies involve a fairly even mix of novice, intermediate and specialist participants. However, the authors also find that CIS research is dominated by exploratory studies, leaves it largely unexplored in what ways the findings of a study may be specific to the particular study setting, appears to assign primacy to precision at the expense of generalizability, struggles with investigating how CIS activities extend over time and provides data about behavior to a larger extent than about reasons, experiences and especially outcomes. Research limitations/implications: The major implication of this review is its identification of the need for a shared model to which individual CIS studies can contribute in a cumulative manner. To support the development of such a model, the authors discuss a model of the core CIS process and a model of the factors that trigger CIS. Originality/value: This study assesses the current state of CIS research, provides guidance for future CIS studies and aims to inspire further methodological discussion.